ОСОБЕННОСТИ ИСПОЛЬЗОВАНИЯ УНИВЕРСАЛЬНОГО МИФА В ЛИТЕРАТУРЕ - Тлеубергенова, Р.Р. (SCIENCE and SOCIETY, 2023)
The article discusses the use of mythological figurative forms in fiction.
Keywords: myth; literary text; universal values; plots; literary genres